2020
DOI: 10.1001/jamanetworkopen.2020.4928
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Value-Driven Selective Attention in Young Children With Autism Spectrum Disorder

Abstract: IMPORTANCE Enhanced selective attention toward nonsocial objects and impaired attention to social stimuli constitute key clinical features of autism spectrum disorder (ASD). Yet, the mechanisms associated with atypical selective attention in ASD are poorly understood, which limits the development of more effective interventions. In typically developing individuals, selective attention to social and nonsocial stimuli is associated with the informational value of the stimuli, which is typically learned over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…Longer P200 latency suggests a slower processing of visual input in autistic participants (Portella et al, 2012) or an over‐processing of information needed for accurate stimuli differentiation (Sokhadze et al, 2009). Reduced selective attention to socially meaningful stimuli has been previously described in ASD (Tyndall et al, 2018; Wang et al, 2020), and our results add to such evidence, by suggesting that less accurate AI in ASD may derive from dysfunction in early stages of selective attention to stimuli that are necessary to aptly anticipate the outcome of the strip. This results in ineffective discrimination between socially relevant and socially irrelevant stimuli and increased processing time (reflected in increased P200 latency) (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Longer P200 latency suggests a slower processing of visual input in autistic participants (Portella et al, 2012) or an over‐processing of information needed for accurate stimuli differentiation (Sokhadze et al, 2009). Reduced selective attention to socially meaningful stimuli has been previously described in ASD (Tyndall et al, 2018; Wang et al, 2020), and our results add to such evidence, by suggesting that less accurate AI in ASD may derive from dysfunction in early stages of selective attention to stimuli that are necessary to aptly anticipate the outcome of the strip. This results in ineffective discrimination between socially relevant and socially irrelevant stimuli and increased processing time (reflected in increased P200 latency) (Wang et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The free‐viewing study design reliably captured how long the participants dwelled on specific ROIs (e.g., face, mouth). Nonetheless, our prior work (Chawarska & Shic, 2009; Wang, Chang, & Chawarska, 2020) has shown that intact attention does not always guarantee that the key information contained in the displays is learned and remembered if the mechanisms responsible for the processing of such information are not functioning properly. Thus, to fully understand factors responsible for language delays in infants with ASD and in the unaffected high‐risk siblings, future studies should examine processing of audiovisual prosodic and speech cues across the autism risk spectrum at the behavioral and neurophysiological levels.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although attention enables learning in general, it does not guarantee that learning will take place. Indeed, several recent studies examining different forms of learning in ASD demonstrated that while toddlers with ASD may attend to faces during learning tasks, they are less likely than control groups to abstract their invariant features (Chawarska & Shic, 2009; Wang et al, 2018; Wang et al, 2020). Thus, it remains to be determined if the typical patterns of attention to puppets in ASD translate into learning.…”
Section: Discussionmentioning
confidence: 99%